Proposed interior design scheme for Atikah Songket Boutique at Lot 93 Jalan Maarof Off Jalan Bangsar, Bangsar Baru 51900, Kuala Lumpur / Siti Aisyah Awalluddin - Awalluddin, Siti Aisyah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed Interior Design Scheme for Atikah Songket Boutique at Lot 93, Jalan Maarof, Off Jalan Bangsar, Bangsar Baru, 59100, Kuala Lumpur. Atikah Songket is a very well-known shop in producing quality textiles especially songket, located in Taman Tun Dr. Ismail, Kuala Lumpur. Atikah’s Songket was opened in 2003 and affiliated by YB Tan Sri Rafidah Aziz. Songket is basically a fabric that belongs to the brocade family of textiles of Indonesia, Malaysia and Brunei. It is hand-woven in silk or cotton, and intricately patterned with gold or silver threads. The metallic threads stand out against the background cloth to create a shimmering effect. In the weaving process the metallic threads are inserted in between the silk or cotton weft (latitudinal) threads. The aim of this project is to introduce and educate people from all over the world to see and appreciate the Malay’s traditional textiles, inherited by our ancestors by opening a boutique specifically for songket materials. The site analysis has been chosen based on potentials to open a songket boutique. The site chosen should give a big impact on opening a very conceptual design that I would like to propose. Through the proposed new interior design scheme of songket boutique centre for Atikah Songket will achieve its objective which is to promote the songket textiles world-wide.